A case of wet purpura due to etoricoxib induced thrombocytopenia - Manappallil, Robin George; Krishnan, Vinod (Asian Journal of Medical Sciences, 2016)
Etoricoxib is a selective cyclo-oxygenase 2 inhibitor, commonly used in treatment of rheumatoid arthritis, gout and back pain. Pretibial edema and erythema, gastric irritation and risks of cardiovascular and cerebrovascular thrombotic events are some of the reported adverse effects due to etoricoxib. This case report is regarding a patient who presented with wet purpura following etoricoxib intake. Drug induced thrombocytopenia is an unreported side effect of etoricoxib. Asian Journal of Medical Sciences Vol.7(5) 2016 135-137